The Relationship between Inter-Arm Blood Pressure Difference and Coronary Artery Disease Severity Calculated by the SYNTAX Score - Gündüz Durmuş; Erdal Belen; Akif Bayyigit; Muhsin Kalyoncuoğlu; Mehmet Mustafa Can (International Journal of Hypertension)
Objectives. The inter-arm systolic blood pressure difference (IASBPD) is closely related to cardiovascular mortality and morbidity. The SYNTAX score indicates the extent and complexity of coronary artery disease, which are determined by coronary angiography. The aim of our study is to examine the relationship between the IASBPD (which is easily calculated in routine practice) and the SYNTAX score. Methods. 104 patients were included in this cross-sectional study. The IASBPD was calculated by blood pressure measurements obtained simultaneously from both arms. The SYNTAX score was calculated by coronary angiography. Results. Patients were divided into two groups: those with a high SYNTAX score (≥20) and those with a low SYNTAX score (<20). The mean IASBPD values were significantly higher in the group with a high SYNTAX score (≥20) (p<0.001). The patients with IASBPD≥10 were more likely to have a high SYNTAX score compared to the patients with IASBPD<10 (p<0.001). Multiple logistic regression analysis revealed that only the IASBPD values were found to be independently associated with high SYNTAX score (OR: 1.717 (CI: 1.307-2.257), p<0.001). Conclusion. The IASBPD values obtained by only blood pressure measurements are closely related to the extent of coronary artery disease.